2020
DOI: 10.1038/s41598-020-71969-w
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the Hop TPR2A domain and investigation of target druggability by NMR, biochemical and in silico approaches

Abstract: Heat shock protein 90 (Hsp90) is a molecular chaperone that plays an important role in tumour biology by promoting the stabilisation and activity of oncogenic ‘client’ proteins. Inhibition of Hsp90 by small-molecule drugs, acting via its ATP hydrolysis site, has shown promise as a molecularly targeted cancer therapy. Owing to the importance of Hop and other tetratricopeptide repeat (TPR)-containing cochaperones in regulating Hsp90 activity, the Hsp90-TPR domain interface is an alternative site for inhibitors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Those types of cancer that rely both on Hsp70–Hsp90-mediated protein folding and proteasome-mediated protein degradation may be particularly vulnerable since the inhibition of Hop reduces the proteasomal activity, which itself is an already established anti-cancer target. Some compounds have been demonstrated to inhibit the interaction between Hsp90 and the TPR2A domain of Hop [ 51 , 187 , 188 ]. The challenge will be to develop inhibitors that are as specific as possible for the interaction of Hop with either Hsp70 or Hsp90, without affecting the interactions of the latter with other TPR-containing co-chaperones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those types of cancer that rely both on Hsp70–Hsp90-mediated protein folding and proteasome-mediated protein degradation may be particularly vulnerable since the inhibition of Hop reduces the proteasomal activity, which itself is an already established anti-cancer target. Some compounds have been demonstrated to inhibit the interaction between Hsp90 and the TPR2A domain of Hop [ 51 , 187 , 188 ]. The challenge will be to develop inhibitors that are as specific as possible for the interaction of Hop with either Hsp70 or Hsp90, without affecting the interactions of the latter with other TPR-containing co-chaperones.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, structurally, the TPR domains are highly organized α-helices [ 47 ]. The TPR1, TPR2A, and TPR2B domain structures of yeast and human Sti1/Hop were evaluated either by X-ray diffraction or solution NMR [ 16 , 49 51 ]. These studies experimentally confirmed the predicted α-helical structures of the TPR domains of Hop.…”
Section: Structure Of Hopmentioning
confidence: 99%
“…Interestingly, using combined in silico and biochemical approaches, the TPR2A domain of the protein Hop was turned into a druggable target. 45 Indeed, authors designed an organic ligand that binds the HSP90 recognition site through contacts with the carboxylate-clamp residues. Similarly, Dictyoceratin-A and -C are two inhibitor molecules that bind the TPR1 region of RPAP3.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Recently, Darby et al mimicked key native "carboxylate clamp" interactions between Hsp90 and its TPR co-chaperones and designed several compounds that block the interaction between Hop TPR2A and Hsp90 C-terminal MEEVD peptide after the failure of AlphaScreen high-throughput screening [146]. The binding of these compounds to the Hop TPR2A domain was confirmed by mapping 1 H- 15 N HSQC chemical shift perturbations to their new reported NMR solution-state structure of Hop TPR2A.…”
Section: Hsp90-hop Interactionmentioning
confidence: 99%